FORCE MAJEURE AND FRUSTRATION OF CONTRACTS DURING PANDEMIC COVID-19 - Muhammad Hazim Ismail; Fadillah Ismail (Jurnal Penyelidikan Sains Sosial, 2021)
The COVID-19 pandemic and resulting government and business response hascaused disruption and consequences that many were unprepared to deal with. In anemployment law context, one of the issues that emerged from these uncertainties relates to theperformance of contractual obligations. Herewith, more and more businesses andorganisations are now inevitably looking at their contracts to see what impact the coronavirusoutbreak will have and how they can mitigate and navigate the challenges brought by thepandemic. In this alert, this paper will briefly discuss the impact of pandemic Covid-19outbreak on the performances of contract, in two situations, one where the contract contains aforces majeure clause and the other is frustration of contracts